Pengaruh Intensitas Aset Tetap, Inventory Intensity Dan Kebijakan Utang Terhadap Agresivitas Pajak - Lia Ningrum; Rakhmawati Oktavianna (CV. ITTC INDONESIA, 2024)
The study aims to empirically demonstrate the impact of fixed asset intensity, inventory intensity, and debt policy on tax aggressiveness. The type of research used is quantitative. The type of data used in this study is secondary data in the form of annual financial statements published on the Indonesian Stock Exchange (BEI) for the for the period 2018–2022. The population of this research is non-cyclical consumer sector companies with non-cyclical sampling using prospective sampling. The number of companies that are taken as samples in this study is 32, with a period of study of five years, so we obtained observation data for as many as 160. Data processing using the Eviews 12 program involved collecting related data and then analyzing descriptive statistics, model conformity tests, classical assumption tests, panel data regression analysis, F statistics tests, t statistical tests, and determination coefficients. Result F states that fixed asset intensity, inventory intensity, and debt policy simultaneously influenced tax aggressiveness